THERMAL HISTORIES FROM THE CENTRAL ALBORZ MOUNTAINS, NORTHERN IRAN: IMPLICATIONS FOR THE SPATIAL AND TEMPORAL DISTRIBUTION OF DEFORMATION IN NORTHERN IRAN - Guest B.; Grove M.; Axen G.J.; Lam P.S.; Stockli D.F.; Hassanzadeh J. (My University, 2006)
We integrate new and existing thermochronological, geochronological, and geologic data from the western and central Alborz Mountains of Iran to better constrain the late Cenozoic tectonic evolution of northern Iran in the context of the Arabia-Eurasia collision. New data are presented for two granitic plutons north of the Alborz Range crest. Additional new apatite (U-Th)-He data are also presented for volcanic, intrusive, and detrital apatite grains from two transects south of the range crest. Our most definitive results include zircon and apatite (U-Th)-He and limited K-feldspar 40Ar/39Ar thermal history data from the Cretaceous (ca. 98 Ma) Nusha pluton that reveal that the Alborz basement underwent generally slow denudation (~0.1 km/m.y.) as late as 12 Ma with more accelerated exhumation (~0.45 km/m.y.) that likely began shortly after 12 Ma. The Lahijan pluton, a late Neoproterozoic-Cambrian basement exposure near the Caspian shore, records apatite (U-Th)-He closure at 17-13 Ma. Additional (U-Th)-He results from detrital apatites sampled along two separate horizontal transects all consistently yielded latest Miocene to Pliocene apparent ages that imply that even supracrustal cover rocks within the Alborz have undergone significant, regionally extensive exhumation. Overall, our data are consistent with ~5 km of regionally extensive denudation since ca. 12 Ma. The onset of rapid exhumation in the Alborz at ca. 12 Ma appears to be consistent with other timing estimates that place the onset of the Arabia-Eurasia collision between 14 and 10 Ma. © 2006 Geological Society of America.
Keywords: (U-TH)-HE; ALBORZ MOUNTAINS; COLLISION; EXHUMATION; IRAN; THERMOCHRONOLOGY; Cretaceous; Neoproterozoic; Pliocene; Miocene; Mesozoic::Cretaceous; Мезозой::Меловая; Precambrian::Proterozoic::Neoproterozoic; Докембрий::Протерозой::Неопротерозойская; Cenozoic::Neogene::Pliocene; Кайнозой::Неоген::Плиоцен; Cenozoic::Neogene::Miocene; Кайнозой::Неоген::Миоцен